Peningkatan Kualitas dan Efisiensi Pengiriman Kargo Udara di PT Ritra Cargo Cabang Denpasar - Yulihapsari, Ika Utami; Saribanon, Euis; Silalahi, Dapot Hamonangan; Nasrullah, Nasrullah; Yuliantini, Yuliantini (Jurnal Abdimas Transportasi & Logistik, 2024)
This Community Service (PKM) activity was carried out at PT Ritra Cargo Denpasar branch with the aim of improving the quality and efficiency of air cargo shipments through the implementation of better packaging procedures and more accurate document management. The company faced issues such as packaging damage, shipping delays, and offloading, which affected customer satisfaction and operational performance. The method of implementation included training the operational staff on packaging standards, document management, and more efficient verification procedures. The results showed a significant reduction in packaging damage, shipping delays, and offloading, with an increase in customer satisfaction as reflected by higher satisfaction ratings. Thus, the training and implementation of new procedures have successfully improved PT Ritra Cargo's operational efficiency and contributed to enhancing the quality of air cargo shipment services. This activity also contributes positively to the development of logistics knowledge, particularly in the effective management of shipments and packaging